Understanding site selection of for-profit educational management organization charter schools - Jin Lee (Arizona State University, 2018)
The rise of for-profit EMOs often becomes evidence of substantial shifts in the governance of education, through which schooling may become privatized and commercialized. This study is designed to understand the economic behavior of for-profit educational management organization charter schools, by focusing on their site selection decisions as a critical factor in making a profit. Using the locations of for-profit EMO charter schools in Michigan, the study examines determinants of the location decision on charter school markets, with the choice set of potential school districts. This research finds changes of the odds ratio in the percentage of for-profit EMO charter schools, logged expenditures per pupil, and in the proportions of African-American populations, populations who have experienced higher education, and unemployed populations. Provided that for-profit EMO charter schools make a site selection decision according to areas with certain characteristics, the spatial disparity of access to charter schools can raise issues concerning unequal educational opportunities.